Grain size effect on magnetic properties of REMnO3 (RE = Pr, Nd) - Dyakonov, V.; Szytuła, A.; Baran, S.; Dyakonov, K.; Zubov, E.; Kravchenko, Z.; Dul, M.; Duraj, R.; Bażela, W.; Szymczak, H. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2013)
X-ray diffraction and magnetic using dc and ac methods measurements of the polycrystalline and nanosize REMnO3 (RE = Pr, Nd) powdered samples have been performed. The nanosize manganites were synthesized with a sol-gel method at different (800, 850 and 900 °C) temperatures. The average size of synthesized nanoparticles (from 56 to 89 nm) and polycrystalline powders (above 200 nm) was estimated using the x-ray diffraction data. All the compounds studied crystallize in the orthorhombic crystal structure (space group Pnma) at room temperature with smaller values of the lattice parameters in the nanosamples. The temperature-dependent ac magnetic susceptibilities show a sharp high-temperature peak connected with Mn magnetic moments ordering. The low-temperature maximum of magnetic susceptibility is proposed to be due to the polarization of the rareearth sublattice by an effective exchange field of the Mn ordered sublattice. The antiferromagnetic ordering of Mn sublattice and paramagnetic Curie temperatures as well as the magnetic moment values for the nanosize samples were found to be smaller than those for polycrystalline sample.